2010
DOI: 10.1002/etc.254
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between biotic ligand model‐based water quality criteria and avoidance and olfactory responses to copper by fish

Abstract: The U.S. Environmental Protection Agency's (U.S. EPA) water quality criteria for Cu were tested to determine whether they protect fish against neurophysiological impairment. From published studies with rainbow trout (Oncorhynchus mykiss), Chinook salmon (Oncorhynchus tshawytscha), coho salmon (Oncorhynchus kisutch), and fathead minnows (Pimephales promelas), 20% inhibition concentrations (IC20s) were calculated for avoidance of Cu-containing water and for impairment of electroencephalogram (EEG) and electro-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(86 citation statements)
references
References 29 publications
2
83
1
Order By: Relevance
“…This assumption is not always true, especially with anadromous or other migratory species which need to transit downstream conditions in order to complete their life cycles. Anadromous salmon and steelhead use olfactory cues to return to their natal streams to spawn (Quinn, 2005), and Cu can disrupt chemoreception at sublethal concentrations Meyer and Adams, 2010). Declines of returning adult Pacific salmon also led to decreased delivery of marine-derived nutrients to streams, and locations with no or few salmon carcasses may in turn have lower productivity than streams with more abundant carcasses (Ebel et al, 2014).…”
Section: Sampling Issuesmentioning
confidence: 99%
“…This assumption is not always true, especially with anadromous or other migratory species which need to transit downstream conditions in order to complete their life cycles. Anadromous salmon and steelhead use olfactory cues to return to their natal streams to spawn (Quinn, 2005), and Cu can disrupt chemoreception at sublethal concentrations Meyer and Adams, 2010). Declines of returning adult Pacific salmon also led to decreased delivery of marine-derived nutrients to streams, and locations with no or few salmon carcasses may in turn have lower productivity than streams with more abundant carcasses (Ebel et al, 2014).…”
Section: Sampling Issuesmentioning
confidence: 99%
“…They concluded that chronic BLM-based Cu criteria were protective of the olfactory IC20 values in all 14 waters (Figure 1) and that the acute BLM-based criteria were protective in all but 2 waters. In contrast to the BLM-based Cu criteria, the hardness-based Cu criteria still in use by US states have been shown to be less consistently protective of olfactory impairment based on a comparison of hardness-based Cu criteria to empirical IC20 values for olfactory impairment and avoidance (Meyer and Adams 2010). Meyer and Adams (2010) also parameterized an olfactory-based BLM that can be used to estimate olfactorybased Cu IC20 values for waters with varying chemistry.…”
Section: Protectiveness Of Copper Criteriamentioning
confidence: 99%
“…In contrast to the BLM-based Cu criteria, the hardness-based Cu criteria still in use by US states have been shown to be less consistently protective of olfactory impairment based on a comparison of hardness-based Cu criteria to empirical IC20 values for olfactory impairment and avoidance (Meyer and Adams 2010). Meyer and Adams (2010) also parameterized an olfactory-based BLM that can be used to estimate olfactorybased Cu IC20 values for waters with varying chemistry. DeForest et al (2011) used the olfactory-based BLM to estimate Cu IC20 values for olfactory impairment based on the surface water chemistry of 133 western US streams.…”
Section: Protectiveness Of Copper Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of competing cations have been considered on the basis of empirical regressions of effect concentrations under various conditions. These effects as calculated by the BLM appear to account for the response to copper by fish as a function of varying water composition (Meyer and Adams, 2010). A recent report on metals environmental risk assessment guidance summarizes the speciation approaches both for metals in the water and sediment compartment (ICMM, 2007).…”
Section: Applications Of Simple Models For Bioavailability To Water Qmentioning
confidence: 99%